Minat Melanjutkan Studi Ke Perguruan Tinggi DitinjauDari Persepsi Peluang Kerja Dan Latar BelakangKondisi Ekonomi Orang Tua Pada Siswa SMKMuhammadiyah 3 Nogosari - Solehudin, Amin, Dra. Titik Asmawati, SE,M.Si (2016)
The research is to know the interest pursue studies to college in terms of perception of employment opportunities and background of the economy parents on the student SMK Muhammadiyah 3 Nogosari Boyolali either partiqlly or simultancously. The type of the research is quantitative associative.the population of this research were 121 students of tenth and eleventh grade at SMK Muhammadiyah 3 Nogosari Boyolali. The sample were 89 students taken by using proportional random sampling. The technique of data collection by using methods now that it has been tested with test validity and reliability tests. Data analysis technique used is multiple regression, t-test, f-test, the relative contribution and effective contribution. The conclusion that can be drawn from this study are:1) There was significan influence between perception of employment opportunities to shoose a major interest in college by t test was obtained tcount > ttable that is 2,997 >1,988 and significant value < 0,005 is 0,025. 2 ) There was significan influence between background of the economy parents to choose a major interest in college by t test was obtained tcount > ttable that is 6,885 >1,988 and significant value < 0,005 is 0,025.3) There is a significant relationsip between perception of employment opportunities, background of the economy parents to shoose what interest college majors based test known f, fcount > ftable is 121,967 > 3,103 with significant value 5%. The result of the conclution of the value (R2)acquired 73,9% interest pursue studies to college influenced by the perception of employment opportunities and background of the economy parents remaining 26,1% is influenced by other variables not examined in this research.